(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The study of social stratification is basically the study of why and how some categories of people are thought to be better than others and of the cones of people’s tendency to rank each other for both themselves and for their societies. It occurs when inequalities between positions and task become widely institutionalized those who occupy highly rewarded positions are able to create circumstances that allow their children to occupy similarly important and rewarding position when they mature. Conversely, those opportunities that would allow them to rise in the stratification system (Mayer Buckley, 11970) in a system of stratification, differences are passed on through the generations.